The Influence of Hospital Management Information Systems and Organizational Culture on Employee Performance - Andi Pratama Putra (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2025)
Hospital Management Information System (SIMRS) is an information communication technology system that processes and integrates the entire service process flow in a Hospital in the form of a coordination network, reporting and administrative procedures to obtain information accurately and precisely, and is part of the Health Information System. Data from the Ministry of Health (Ministry of Health states the use of the SIMRS application (hospital management information system), reporting that 1257 out of 2588 (or around 48%) hospitals in Indonesia have a functional SIMRS. There are 128 hospitals (5%) that report that they already have a SIMRS but are not yet running functionally. It turns out that there are still 425 hospitals (16%) that do not have a SIMRS. However, there are still 745 hospitals (28%) that have not reported whether they have a SIMRS or not. This study uses a quantitative descriptive method with a cross-sectional study design. The sampling technique used in this study was simple random sampling, which was carried out in June 2024 with a sample of 51 people regarding this study. The results of the study showed that organizational culture has an influence on employee performance. It is hoped that with this study, hospitals can create an organizational culture related to employee performance.